The early use of insulin in type 2 diabetes - PHILIP LEVY (Сахарный диабет)
60?70% of all patients with Type 2 Diabetes Mellitus will ultimately require insulin therapy for the management of their diabetes. Irisulin may be used alone, or in combination with oral agents. The early use of insulin can be very important in decreasing the incidence of micro-vascular complications and in helping to delay the onset of macro-vascular complications. The United Kingdom Prospective Diabetes Study and the Kumamoto Study have shown the beneficial effects of good glucose control in type 2 diabetes mellitus. The DECODE study has related overall mortality to the level of glucose control and specifically to the postprandial glucose. The American Association of Clinical Endocrinologists has established a goal of 6.5% or less for HgbAlc. The appropriate use of insulin will allow us to achieve this goal without causing the patient any undue harm. There are many barriers to insulin therapy including psychological barriers of both the patient and the doctor, and unrealistic fears of both insulin therapy and therapy with self-administered injections. These barriers will be discussed as well as methods to overcome them. Insulin therapy is beneficial and has no long term adverse effects. The incidence of severe hypoglycemia is extremely low in type 2 diabetes. Weight gain is minimal. Insulin therapy by reducing glucose toxicity may also increase the effectiveness of oral anti-hyperglycemic agents. The physician taking care of patients with diabetes should be aggressive and should have no fears of initiating insulin therapy. Insulin dosage is flexible and good control is possible in most patients. The most common use of insulin in type 2 diabetes is as an add-on to oral agents if control with oral agents alone is unsatisfactory. Frequently this involves the use of a single dose of intermediate or long acting insulin or an insulin mixture in the evening. If control is not attained with a single dose, then the patient can be placed on an insulin mixture 2 or 3 times a day. An alternative would be a short acting insulin analogue prior to each meal with a longer acting insulin given 1 or 2 times a day. Titration schedules for insulin dosing will be presented. Insulin available in Russia will be listed along with some guidelines on using these insulins. Increasing the use of insulin and starting insulin earlier in type 2 diabetes will lead to better control of diabetes, increased patient compliance, and decreased long-term complications of diabetes mellitus.